The Role of Heparin in Lung Cancer - Abu Arab, Walid; Kotb, Rami; Sirois, Marco; Rousseau, Éric (Journal of Neoplasms, 2017)
Non-small cell lung cancer is a major health problem worldwide. Surgery is still the mainstay of treatment especially in early stages of the disease. Despite the fact that surgery is the potentially curative treatment, the recurrence and mortality rates are still high specifically with more advanced stages of cancer. Heparin has been suggested to have a positive impact on the outcome of various cancers through its anticoagulants properties and; in some instances; due to their antitumor activity. Recently, the molecular mechanisms of tumor cell spreading have been recognised. Metastasis is a complex process that could be therapeutically affected wherever certain extra-cellular matrix proteins could play an important role in prevention of tumor cell migration and invasion. Experimental studies have shown decreased metastases development after heparin use in rat models. We have reviewed the literature to study the role of anticoagulants in cancer patients in general and in patients with Non Small Cell Lung Cancer (NSCLC) specifically.
Keywords: Heparin; Lung Cancer; NSCLC; Anticoagulants; Metastasis